Biology teacher needs for integrating deep learning into project-based learning in Muhammadiyah schools - N. Nurwidodo; Iin Hindun; Sri Wahyuni; Hawaree Lambensa (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: Deep learning and project-based learning are both expected to strengthen students’ critical thinking, creativity, and collaboration, yet many teachers still implement project-based learning only at a procedural level. Objectives: This study aimed to analyze biology teachers’ needs for integrating deep learning into project-based learning (DL-PjBL) in Muhammadiyah schools in Batu City, Indonesia. Methods: A descriptive survey design was used with 40 biology teachers selected purposively from 95 teachers across Muhammadiyah elementary, junior high, and senior high schools. Data were collected using questionnaires, interviews, observations, lesson-document reviews, and student-profile data, then analyzed descriptively using quantitative summaries and qualitative interpretation. Results: Students’ critical thinking, creative thinking, and collaboration were generally at low-to-basic levels. Most teachers reported limited understanding of deep learning (80%), only superficial familiarity with project-based learning (75%), limited awareness of DL-PjBL integration (80%), and strong demand for practical guidance on principles, syntax, worksheets, media, and classroom examples (75%–90%). Conclusion: Teachers urgently need a practical DL-PjBL framework that explains the rationale, principles, operational procedures, and expected impacts of the model to support more meaningful, mindful, and joyful learning.